1999
DOI: 10.1016/s0014-5793(99)00843-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a pollen‐specific sucrose transporter‐like proteinNtSUT3 from tobacco

Abstract: Pollen cells are symplasmieally isolated during maturation and germination. Pollen therefore needs to take up nutrients via membrane carriers. Physiological measurements on pollen indicate sucrose transport in the pollen tube. A cDNA encoding a pollen-specific sucrose transporter-like protein NtSUT3 was isolated from a tobacco pollen cDNA library. NtSUT3 expression is detected only in pollen and is restricted to late pollen development, pollen germination and pollen tube growth. Altogether these data indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…The hub genes identified in the co-expression network were annotated as encoding a sucrose-proton symporter 2 ( C.cajan_35396 ), a pollen specific SF3 protein ( C.cajan_07765 ) and an uncharacterized protein ( C.cajan_28171 ). C.cajan_35396 gene encoding a putative H + symporting sucrose transporter protein 2 has been suggested to be involved during pollen maturation in mediating sucrose uptake in pollen grains (Lemoine et al , 1999). In the co-expression network generated, each of the two hub genes ( C.cajan_35396 and C.cajan_28171 ) was connected to all the other 27 genes, which encoded serine threonine protein kinases ( C.cajan_18757 , C.cajan_20002 , C.cajan_07067 ), pectinesterase inhibitors ( C.cajan_10140 , C.cajan_04310 , C.cajan_46391 ), pectate lyase 3 ( C.cajan_ 44741 , C.cajan_27022 ), pollen-specific proteins ( C.cajan_02582 , C.cajan_07765 , C.cajan_11513 ), Olee1-like ( C.cajan_31667 , C.cajan_32224 ), L-ascorbate oxidase homolog ( C.cajan_19226 , C.cajan_20191 ), ATPase 8 ( C.cajan_45656 ), β-galactosidase 13 ( C.cajan_32927 ), polygalacturonase ( C.cajan_04312 ), phosphatidylinositol transfer protein ( C.cajan_35458 ), boron transporter 6 ( C.cajan_04911 ), formin-like protein 5 ( C.cajan_32517 ), aldose 1-epimerase ( C.cajan_31220 ), and uncharacterized proteins (C .cajan_ 04239 , C.cajan_24722 , C.cajan_02776 , C.cajan_27282 ).…”
Section: Resultsmentioning
confidence: 99%
“…The hub genes identified in the co-expression network were annotated as encoding a sucrose-proton symporter 2 ( C.cajan_35396 ), a pollen specific SF3 protein ( C.cajan_07765 ) and an uncharacterized protein ( C.cajan_28171 ). C.cajan_35396 gene encoding a putative H + symporting sucrose transporter protein 2 has been suggested to be involved during pollen maturation in mediating sucrose uptake in pollen grains (Lemoine et al , 1999). In the co-expression network generated, each of the two hub genes ( C.cajan_35396 and C.cajan_28171 ) was connected to all the other 27 genes, which encoded serine threonine protein kinases ( C.cajan_18757 , C.cajan_20002 , C.cajan_07067 ), pectinesterase inhibitors ( C.cajan_10140 , C.cajan_04310 , C.cajan_46391 ), pectate lyase 3 ( C.cajan_ 44741 , C.cajan_27022 ), pollen-specific proteins ( C.cajan_02582 , C.cajan_07765 , C.cajan_11513 ), Olee1-like ( C.cajan_31667 , C.cajan_32224 ), L-ascorbate oxidase homolog ( C.cajan_19226 , C.cajan_20191 ), ATPase 8 ( C.cajan_45656 ), β-galactosidase 13 ( C.cajan_32927 ), polygalacturonase ( C.cajan_04312 ), phosphatidylinositol transfer protein ( C.cajan_35458 ), boron transporter 6 ( C.cajan_04911 ), formin-like protein 5 ( C.cajan_32517 ), aldose 1-epimerase ( C.cajan_31220 ), and uncharacterized proteins (C .cajan_ 04239 , C.cajan_24722 , C.cajan_02776 , C.cajan_27282 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sucrose transporters are important proteins for the translocation of sucrose from source to sink organs (Smeekens 2000). Lemoine et al (1999) identified a pollen-specific sucrose transporter ( NtSUT3 ) in tobacco, which participates in pollen development and supplies nutrition to pollen tubes. The deletion of the Os SUT1 gene could damage pollen function in rice (Hirose et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Note that the nomenclature of sucrose transporters in Arabidopsis may differ. SUT1 and SUT3 are paralogs in tobacco (Lemoine et al, 1999) the corresponding genes in Arabidopsis are called SUC2 as well as SUC1, 5, 6, 7, 8, and 9. SUT2 has been called SUC3 and SUT4 has been called SUC4.…”
Section: Sucrose Transport and Sut Family Membersmentioning
confidence: 99%